2019
DOI: 10.7202/1061836ar
|View full text |Cite
|
Sign up to set email alerts
|

La réflexivité : entre l’expérience déstabilisante et le changement?

Abstract: Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This means that the different rewritings were beneficial for the students (Colognesi & Lucchini, 2016; Lee, 2011). In addition, we showed that these portfolio rewrites allowed participants to document and conceptualize their practices (Hamilton, 2017; Loughran, 2014), make better connections between theory and practice (Altet et al, 2013), and find ways to improve their teaching practices (Chaubet et al, 2019; Waege & Haugalokken, 2013). In this sense, the writing of the portfolio indeed had a knowledge-weaving role (Hamilton, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This means that the different rewritings were beneficial for the students (Colognesi & Lucchini, 2016; Lee, 2011). In addition, we showed that these portfolio rewrites allowed participants to document and conceptualize their practices (Hamilton, 2017; Loughran, 2014), make better connections between theory and practice (Altet et al, 2013), and find ways to improve their teaching practices (Chaubet et al, 2019; Waege & Haugalokken, 2013). In this sense, the writing of the portfolio indeed had a knowledge-weaving role (Hamilton, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Four criteria (Table 2) were used to measure the development of students’ reflective competence, with reference to the aspects of reflective analysis (Chaubet et al, 2019): observe situations (Criterion 1: describe one’s practices) from new angles, document them to understand their multiple facets (Criteria 2 and 3: make theory-practice links to give meaning and master concepts used) and identify, through progressive analysis, possible solutions and actions (Criterion 4: development over time).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations